ANALISIS PERMINTAAN DAGING SAPI DI SULAWESI TENGGARA (Model Analisis Permintaan Dinamis) - RUSMA, MUHAMMAD; -, SUHARYANTO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The research was conducted in South East Sulawesi and aimed : 1) to identify factors affecting the beef demand, 2) to classify whether beef as normal or luxury goods, 3) to identify other product that have substitution and complementary relationship to beef, 4) to identify whether the number of population and income on beef consumption have positive relationship, 5) to estimate the consumption of beef for 2010. The time series data in the periods for 14 years of 1987-2000 was used for this research. A dynamic model of Ordinary Least Square (OLS) method was used to analyze the data. The result showed that beef demand in South East Sulawesi depended on the price of beef, chicken, fish and consumption of the previous year. A cross price between fish and fried oil was in elastic. A regression coefficient for price of beef was negative but positive for the income, therefore, beef was classified into normal goods. Chicken and fish had substitution relationship and fried oil had complementary relationship to beef. The consumption of beef for 2010 tend to increase and will be higher then that of the previous year.
Keywords: Beef, Demand, Elasticity